Pension schemes in the European Union: Challenges and implications from macroeconomic and financial stability perspectives - Antonio Sánchez Serrano; Tuomo Peltonen (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2020)
Pension schemes have a significant influence on the saving and consumption decisions of households. Similarly, contributions to pension arrangements are substantial expenditures for national governments and also for corporations, depending on the prevailing pension system. Beyond this, pension schemes play an important role in the economy, channelling savings into investments through capital markets. However, demographic factors and the macroeconomic environment (low interest rates, low growth and low productivity) are raising concerns about the sustainability of pension schemes over the long term, in particular for those of a defined benefit type. Their impact on pension schemes and the way to adjust to them have been under the consideration of national and international institutions for some time. In principle, Pillar 1 pension schemes (i.e. those sponsored by the government) would be more affected by demographic factors, whereas the macroeconomic environment would pose a larger challenge to Pillar 2 and 3 pension schemes (i.e. those where the employer and employees contribute to the scheme, and the residual category, respectively). While these vulnerabilities are expected to materialise slowly, they can potentially endanger the sustainability of pension schemes, particularly those operating under a defined benefit structure. The likely outcome of the materialisation of these sources of vulnerabilities implies that, over a long-term horizon, the gap between the income which households expect to receive at retirement and the income which pension schemes are effectively able to pay may become significant. This gap is starting to become visible, in particular for defined benefit occupational pension funds. Actually, for both defined benefit and defined contribution schemes, the macroeconomic environment may lead to effective returns that are lower than expected. In this report, we discuss pension schemes and the related vulnerabilities in terms of their macroeconomic and financial stability impact in the European Union (EU).
Keywords: G23; G28; D15; H55; J32; 330; pensions; financial stability; ageing population; interest rates